Effect of solarization, organic matter, and Trichoderma on the severity of Verticillium wilt in olive trees (Olea europaea L.) and soil inoculum density - Otero, Maria Laura; Roca, Mónica; Zapata, Raúl Lorenzo; Ladux, Jose Luis; Ortiz, J.; Matias, Angel Cesar; Perez, Beatriz Alida (International Society for Horticultural Science, 2018)
VII International Symposium on Olive Growing, San Juan, Argentina